Strengthening producer organizations to increase market access of smallholder farmers in Uganda - Hill, Ruth Vargas; Maruyama, Eduardo; Olapade, Markus; Frölich, Markus (Cambridge University Press, 2021)
Smallholder agriculture in Sub-Saharan Africa is largely exposed to pervasive market failures, translating into missed opportunities and sub-optimal economic behavior. These failures can partly be traced to the importance of economies of scale in procuring inputs and marketing produce, where smallholders face disproportionately high transaction costs. Producer organizations could help to lessen transaction costs; however, only a few farmers in Uganda sell through them. We introduce two interventions aimed at promoting marketing via producer organizations: cash on delivery, and information on sales, and analyze their impacts in an RCT design: We find that providing cash on delivery increases the probability that a member chooses to sell through the group, and hence the volumes bulked by each group. This increase in volumes appears to have enabled groups to secure higher prices for their produce. No significant effect could be found for providing information on sales.